Pensions at a glance 2013. OECD and G20 indicators (Paris, 2013)
"This comprehensive examination of pension systems in OECD and selected non-OECD countries looks at recent trends in retirement and working at older ages, evolving life expectancy, design of pension systems, pension entitlements, and private pensions before providing a series of detailed country profiles."